A drawer-type abdominal window with an acrylic/resin coverslip enables long-term intravital fluorescence/photoacoustic imaging of the liver - Deng Deqiang; Dai Bolei; Wei Jianshuang; Yuan Xuenan; Yang Xiaoquan; Qi Shuhong; Zhang Zhihong (Nanophotonics, 2021)
The liver has a unique vascular structure and regional immunosuppressive characteristics closely linked to the occurrence and development of diseases. There are no long-term, large-field, and high-quality imaging methods to simultaneously obtain the structure of blood vessels and movement activities of immune cells in abdominal organs in vivo. This research developed a drawer-type abdominal window with an acrylic/resin coverslip named DAWarc and applied it to the intravital fluorescence/photoacoustic imaging of the liver for over 10 days. The liver lobe was inserted into the drawer holder of the DAWarc to physically fix the liver, which decreased the imaging artifacts. The acrylic/resin material used as the coverslip has a high compatibility for fluorescence/photoacoustic imaging. Through intravital fluorescence/photoacoustic imaging, information on the structure of hepatic lobules, spatial distribution of nanopomegranate labeled Kupffer cells (KCs), the movement behavior of invariant natural killer T cells, and morphology of KCs were obtained. We also used a self-organizing map neural network to detect tumor metastases in the photoacoustic images automatically. Conclusively, the DAWarc model provided a powerful tool for intravital fluorescence/photoacoustic imaging of the liver; it helped us to better understand the structure of hepatic lobules and the distribution and function of immune cells during the occurrence and development of liver diseases.